(untitled) (Research, Society and Development, 2022)
The elaboration of educational products/processes as a result of the dissertation of a Post-Graduation Program (professional modality) is primordial for the improvement of Brazilian education, bringing academic knowledge closer to the needs of society. Therefore, the present research investigates how the knowledge generated by a professional Post-Graduate Program (PGP) in the Teaching Area of a public University in Pará has been disseminated, identifying which regions of Brazil and the world are interested in these educational products/processes. For this, a documentary research was conducted with the analysis of these educational products/processes produced in the quadrennium 2017/2020, made available on the PGP website and on the eduCAPES Platform. Data collected: the type of educational product/process; number of downloads, viewing ranking by country and city (further arranged in geographic regions). It was found that the analyzed production was visualized in the European, American and Asian continents; and in the countries Brazil, United States and Ukraine; in Brazil the largest number of accesses is from the Southeast region. The most viewed products were educational games. In this context, the dissemination of academic production is vital to meet the demands of society and of teachers/researchers, helping in the solution of everyday problems and professional practice. So, making the products/processes accessible by making them available not only in open access platforms but also in other social media. Present the products in other languages for greater global reach.